An Additional Record of the Lichen Stereocaulon massartianum Hue. (Stereocaulaceae) from Mawphanlur in West khasi Hills District of Meghalaya, India (International Journal of Food and Nutritional Sciences, 2022)
Present study reports the occurrence and distribution of the lichen species Stereocaulonmassartianum Hue. in the locality of Mawphanlur of West Khashi Hill district in Meghalaya.The genus is one of the fruticose lichen group that distributed world widely in tropical to polarzone